Predicting Treatment Cost for Bacterial Diarrhoea at a Regional Hospital in Thailand (Journal of Health, Population and Nutrition, 2009)
The aim of this study was to estimate the treatment cost and formulate a cost-function for bacterial diarÂrhoea among patients in a Thai regional hospital. This study was an incidence-based cost-of-illness analysis from a hospital perspective, employing a micro-costing approach. It covered new episodes of both outÂpatients and inpatients who were diagnosed to have bacterial diarrhoea (ICD-10 code A00-A05) and who received treatment during 1 October 2000-31 July 2003. Retrospective data were collected from medical records of the hospital. The study covered 384 episodes, and the mean age of patients was 24 years. The average treatment costs (at 2002 prices; US$ 1=approximately 40 Thai baht) were US$ 11.29, 76.78, and 44.72 per outpatient episode, inpatient episode, and outpatient/inpatient combined episode respectively. Furthermore, the positive significant predictor variables were: inpatient care, other Salmonella-associated infections, shigellosis, other bacterial intestinal infections, and the health insurance scheme. The fitted model was able to predict greater than 80% of the treatment cost. The estimation of simulated patients demonstrated a wide range of costs, from US$ 10 per episode to US$ 163 per episode. Overall, hospital administrators can apply these results in cost-containment interventions. Key words: Bacteria; Cost-function analysis; Cost and cost analysis; Diarrhoea; Health expenditure; HealthÂcare cost; Retrospective studies; Thailand doi:10.3329/jhpn.v26i4.1886 J Health Popul Nutr 2008 Dec:26(4):442-450